Scanning Electron Microscopy (SEM) Energy Dispersive X-ray Spectroscopy (EDS) Mapping and In-situ Observation of Carbonization of Culms of Bambusa Multiplex. (27th April 2018) - Yordsri, Visittapong; Thanachayanont, Chanchana; Asahina, Shunsuke; Yamaguchi, Yuuki; Kawasaki, Masahiro; Oikawa, Tetsuo; Nobuchi, Tadashi; Shiojiri, Makoto
Abstract: Green culms of bamboo and charcoal of Bambusa multiplex were investigated by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) mapping. A dynamic observation of the initial stage of carbonization was also performed in-situ by heating a radial longitudinal section of the bamboo culm at a rate of 20°C/min up to 500°C. EDS mapping of the green bamboo culms detected Si signals in the harder cells such as the epidermis ( Ep ), cortex ( Cor ) and vascular bundle sheath ( Bs ) and between these cells as silicon oxide particles. Appreciable morphological change of the cells occurred in a temperature range of about 300–400°C due to the decomposition of cellulose that is the main component of the bamboo cells. The charcoal of the bamboo culm has a skin layer which originates from the Ep and Cor and the main central cylinder with many openings that originate from the expanded xylem and phloem holes. During carbonization, the Si atoms in the Ep and Cor were segregated as thin silicon oxide layers onto both the sides of the skin layer and the Si included in the Bs fibers and parenchyma cells accumulated near the walls of the openings.